Assessment of C-reactive Protein and C3 as Inflammatory Markers of Insulin Resistance in Women with Polycystic Ovary Syndrome: A Case-Control Study - S Dehdashtihaghighat; A Mehdizadehkashi; A Arbabi; M Pishgahroudsari; Sh Chaichian (JRI, 2013)
Background: Polycystic ovary syndrome (PCOS), a common endocrine disorder, is associated with infertility, menstrual dysfunction, hirsutism and frequent miscarriages. Insulin resistance, as a major cause of PCOS, represents a disorder with increase in inflammatory markers and risk of type 2 diabetes. We aimed to investigate whether inflammatory markers, including C-reactive protein and C3 (Complement), are related and altered in polycystic ovary syndrome. Methods: A case-control study including forty-two women diagnosed with PCOS, according to Rotterdam criteria, and forty-two healthy controls, matched for body mass index (BMI) and age, was conducted in 2012. C-Reactive protein (CRP) and C3 were assessed as possible determinants of the homeostasis model assessment (HOMA) index. Independent-sample t-test was used to compare the means of the groups in age, BMI, C3, FBS and BS 2hpp (2 hr postprandial glucose) and for CRP, Fasting Insulin and 2 hr Plasma Insulin and HOMA index. Mann-Whitney test and Pearson correlation were used for analyzing the data. The p<0.05 was considered as statistically significant. Results: Levels of plasma CRP (p=0.039), 2 hr pp (p=0.045), Fasting Insulin (p=0.002), 2 hr Plasma Insulin (p=0.002) and HOMA index (p=0.002) were significantly higher in PCOS patients. But C3 was not significantly higher in cases (p=0.885). There was no significant correlation between C3 and CRP with HOMA index. Conclusion: CRP increased significantly in patients with PCOS and was associated with insulin resistance, the most probable cause of PCOS. However, such an association was not found in C3.
Keywords: C3, C-reactive protein, Insulin resistance, Polycystic ovary syndrome